2020
DOI: 10.1021/acs.est.0c04051
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Personal PM2.5 Elemental Constituents and Decline of Kidney Function in Older Individuals: the China BAPE Study

Abstract: Long-term exposure to fine particulate matter (PM 2.5 ) is associated with kidney dysfunction. However, few studies have investigated acute effects of PM 2.5 elemental constituents on renal function. We evaluated associations between personal PM 2.5 and its elemental constituents and kidney function, assessed by an estimated glomerular filtration rate (eGFR) in Biomarkers of Air Pollutants Exposure in the Chinese aged 60−69 study. Seventy one older individuals were visited monthly between September 2018 and Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…In addition, in a general adult Taiwanese population (n = 108,615) with an average ± SD age of 39.1 ± 11.8 years, Zeng et al [47] demonstrated that each 10 µg/m³ increment of PM 2.5 could be significantly associated (p < 0.001) with a 3.18-fold increased risk of an eGFR decline ≥30% (95% CI 2.88 to 3.50). In an elderly population (60 -69 years old; n = 71), the panel study of Fang et al [21] showed that an IQR increment of 31.43 µg/m³ in PM 2.5 exposure was significantly associated (p < 0.05) with a 3.27% eGFR decrease, albeit in a small population size (n = 71).…”
Section: Discussion Egfr For Assessment Of Renal Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, in a general adult Taiwanese population (n = 108,615) with an average ± SD age of 39.1 ± 11.8 years, Zeng et al [47] demonstrated that each 10 µg/m³ increment of PM 2.5 could be significantly associated (p < 0.001) with a 3.18-fold increased risk of an eGFR decline ≥30% (95% CI 2.88 to 3.50). In an elderly population (60 -69 years old; n = 71), the panel study of Fang et al [21] showed that an IQR increment of 31.43 µg/m³ in PM 2.5 exposure was significantly associated (p < 0.05) with a 3.27% eGFR decrease, albeit in a small population size (n = 71).…”
Section: Discussion Egfr For Assessment Of Renal Functionmentioning
confidence: 99%
“…The risk of bias analysis was performed using the Newcastle -Ottowa Scale and articles were ranked accordingly: gaining ≤ 3 stars meant a high risk of bias, ≤ 5 stars an intermediate risk of bias, and ≥ 6 stars a low risk of bias [20]. One article had an intermediate risk of bias [21], while no articles were considered as high risk of bias (Supplementary Table 1).…”
Section: Literature Selection and Assessment Of Risk Of Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a panel study with 76 participants 60–69 years of age in Jinan, China observed that significant declines in eGFR from −1.69% (95% CI: −3.34%, −0.01%) to −3.27% (95% CI: −5.04%, −1.47%) were associated with IQR increases in personal PM 2.5 exposures at different lag periods (from 7–12 to 49–72 hours). 20 Another panel study with 105 children 4–13 years of age in Wuhan, China, showed that personal exposure to PM 2.5 was dose-responsive related to decline in eGFR within lag 2 days with the strongest at lag 0 day [−1.69% (95% CI: −2.27%, −1.10%) in eGFR per 10 μg/m 3 increase in PM 2.5 ]. 22 Gu et al 21 and Wei et al 23 reported that short-term (daily) PM 2.5 exposure was associated with increased risks of hospital admission for kidney diseases based on electronic inpatient records in China (all-age) and the United States (age 65 years or older), respectively.…”
Section: Discussionmentioning
confidence: 99%